2015
DOI: 10.1111/poms.12388
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Limited Supply on a Firm's Bundling Strategy

Abstract: A firm's two-product bundling decision is examined when the supply of one product is limited and consumer valuations are normally distSteckeributed. The firm can choose to sell products separately and/or through a bundle. We find that the impact of limited supply on a firm's bundling decision depends on the correlation between the consumer valuations of the two products as well as the symmetry level of the two products in terms of their attractiveness (how much they are valued by consumers). When the valuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Prasad et al (2010) study bundling under network effects. Three recent papers consider bundling in a distribution channel and show that channel conflict may weaken a firm's incentive to bundle (Bhargava 2012), and bundling can serve as a channel-coordination mechanism (Cao et al 2015a) and may improve firm profit under supply constraint (Cao et al 2015b). Unlike the above papers, we consider agency pricing and are the first to show when and how channel contracts including agency pricing interact with add-on pricing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prasad et al (2010) study bundling under network effects. Three recent papers consider bundling in a distribution channel and show that channel conflict may weaken a firm's incentive to bundle (Bhargava 2012), and bundling can serve as a channel-coordination mechanism (Cao et al 2015a) and may improve firm profit under supply constraint (Cao et al 2015b). Unlike the above papers, we consider agency pricing and are the first to show when and how channel contracts including agency pricing interact with add-on pricing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When PB and MB are compared, MB is more profitable if there are substantial differences (heterogeneity) in the valuation of the second product (Pierce and Winter, 1996). Recently, some studies have extended the bundling studies by incorporating other elements, such as the effect of network externalities (Prasad et al , 2010; Pang and Etzion, 2012) and capacity limit (Cao et al , 2015). In this paper, we extend the existing bundling literature by considering piracy, which is especially relevant to information goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of cooperation between suppliers within a decentralized supply chain was found to influence the bundling decisions and profitability. 6 Cao et al 7 investigated bundling strategies driven by the limited supply of a product. The benefits of such supply-driven bundling strategy depend on the severity of supply limitation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impacts of different bundling strategies, such as pure or mixed, for information products have been compared by Li et al 5 Existing research studies addressing recent directions in the area of bundling have identified a number of factors influencing bundling decisions. Such aspects and considerations include the following: bundling in supply chain, 6,7 product bundling in a distribution channel, 8 optimal composition and pricing, 2 bundling of complementary products, 9 customized bundling, 10 and product heterogeneity and risk considerations. 11 Rao et al 12 investigated emerging trends in product bundling by extending this concept to various new settings.…”
Section: Introductionmentioning
confidence: 99%